MODEL INTEGRASI STEM DAN TURATS DALAM MANAJEMEN KURIKULUM PESANTREN - Nashrullah Nashrullah; Rian Nur Farezi; Fionaldo Satria Devangga; Abdul Hamid (MPI STAI Sangatta Kutai Timur, 2026)
This study examines in depth the holistic-integrative curriculum management model at MTs Pondok Mambaus Sholihin, which aims to synergize modern STEM literacy (scientific, technological, engineering, and mathematical reasoning competencies) with classical Islamic studies or turats (the treasury of religious scholarship rooted in the study of classical texts/kitab kuning). Pesantren-based madrasahs frequently confront epistemic dichotomies and the risk of cognitive overload among santri (Islamic boarding school students) when integrating secular and religious disciplines. Employing a field-based qualitative case study design, data were gathered through participant observation, in-depth interviews with institutional leadership and teaching staff, and a comprehensive document analysis of the Learning Objectives Flow. The findings of this study reveal that curriculum integration is precisely engineered at the planning stage through a